“Make My Burden Lighter”: Depression and Social Support in Persons with Disability in Ghana - Frances Emily Owusu-Ansah; Josephine Nkrumah (Journal of Depression And Therapy, 2017)
Depression in the general population has been associated with inadequate or lack of social support. Evidence from the disability field has been limited. This study investigated the relationship of perceived social support to depression in Persons with Disability (PWDs) using a descriptive survey design. Data was collected from 317 PWDs using the Beck Depression Inventory Scale (BDI) and Multidimensional Scale of Perceived Social Support (MSPSS) and analyzed with Statistical Package for the Social Sciences (SPSS) version 16 software. Findings revealed significant relationship between perceived social support and depression in PWDs and meaningful social support ameliorated severity of depressive symptoms. Though etiology of acquisition of the disability, either by birth or later in life, had less likelihood on being depressed, respondents who acquired their disability later in life had significant depression levels than those who were born disabled. Implications of findings for the treatment of depression in PWDs are discussed.
Keywords: social support